Mekanisme Penerbitan Surat Keputusan KPK Nomor 625 Tentang Alih Status Kepegawaian Sesuai Dengan Perundang-Undangan - Raden Rara Mutiara Wijaya; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Jurnal Discretie, 2022)
This study analyse whether the issuing the Corruption Eradication Commission (KPK) Decree Number 625 regarding the transfer of employment status is under the law. This research is a prescriptive doctrinal or normative legal research with a comparative approach, namely comparing the KPK's decision letter No. 625 of 2021 with Law No. 19 of 2019. The research sources are primary and secondary legal materials while collecting legal materials uses library research. The study results show that the issuing the KPK Decree Number 625 regarding the transfer of employee status is not suitable with the Act. Transferring the status of KPK employees to the state civil apparatus (ASN) should be seen as a transition and not a selection of new employees per the basic provisions of Law Number 19 of 2019. However, in practice, the National Insight Test (TWK) is used to select the status of KPK employees to become government employees. The issuance of Decree Number 1354 of 2021 led to dismissed of KPK employees who failed the National Insight Test (TWK). This violates Law Number 19 of 2019 and the procedure for issuing KPK decisions in article 16 of the Regulation of the Corruption Eradication Commission  Number 12 of 2018.